Briquette Characteristics of Mixed Charcoal of Taro Peel and Rice Husk - Galu Murdikaningrum; Mutiara Putri Utami Susanto; Raden Tarisa Nurhanifah; Mua lifah (Universitas Insan Cendekia Mandiri, 2023)
Petroleum reserves in Indonesia are running low, as well as fossil energy. If these conditions are not handled appropriately and quickly, the Indonesian nation will experience a petroleum crisis. Biomass briquettes are made from a combination of rice husks, taro husks, and a tapioca flour adhesive, and they will be produced as a byproduct of Indonesia's extensive agricultural sector and the growing taro industry. The use of taro skin in conjunction with other raw materials gives this study an element of originality. The purpose of this research is twofold: to disseminate knowledge about the potential of biomass waste, and to analyze how different biomass waste mixtures affect the briquettes SNI-required properties. An experimental approach was used for this study. In this experiment, three different weight ratios of taro husks to rice husks (KT:50%, KT:75%, and KT:100%) were employed as the primary raw materials. Five-and-a-half percent of the briquette dough's overall weight comes from tapioca flour's role as an adhesive. Preparation of briquette materials, carbonization, briquetting, and testing for biomass briquette characteristics are the first steps in the study approach. The calorific value, moisture, ash, volatile matter, binding carbon, and density tests are all part of this battery of analyses. The highest grade briquettes have a calorific value of 3,993.92 cal/g and are made from 100% KT briquettes. KT briquettes with a 75% moisture content are the highest grade briquettes available. At 22.90%, KT briquettes have the lowest ash level of any high-quality briquettes. Briquettes made from 100 percent KT, or 0.09 percent volatile matter, are the highest grade available. KT briquettes, which have a bonded carbon content of 74.59%, are the highest grade option. 50% KT briquettes, with a density of 0.48 g/cm3, are the highest grade briquettes available.